Sorry I'm Late, I Didn't Want to Come : One Introvert's Year of Saying Yes - Pan, Jessica (Kansas City, Missouri : Andrews McMeel Publishing, 2019)
"What would happen if a shy introvert lived like a gregarious extrovert for one year? If she knowingly and willingly put herself in perilous social situations that she'd normally avoid at all costs? Writer Jessica Pan intends to find out. With the help of various extrovert mentors, Jessica sets up a series of personal challenges (talk to strangers, perform stand-up comedy, host a dinner party, travel alone, make friends on the road, and much, much worse) to explore whether living like an extrovert can teach her lessons that might improve the quality of her life. Chronicling the author's hilarious and painful year of misadventures, this book explores what happens when one introvert fights her natural tendencies, takes the plunge, and tries (and sometimes fails) to be a little bit braver"--Provided by publisher.
Includes bibliographical references.
Keywords: Pan, Jessica; Introverts -- Humor; Extraversion -- Humor; Extraversion; Introverts; Humor; Self-help publications; Self-help publications